Prevalence and determinants of maternal near miss in Ethiopia: a systematic review and meta-analysis, 2015-2023 - Abraham Negash; Addisu Sertsu; Dechasa Adare Mengistu; Aklilu Tamire; Adisu Birhanu Weldesenbet; Mesay Dechasa; Kabtamu Nigussie; Tilahun Bete; Elias Yadeta; Tegenu Balcha; Gebiso Roba Debele; Deribe Bekele Dechasa; et al. (BMC, 2023)
Abstract Background One of the most challenging problems in developing countries including Ethiopia is improving maternal health. About 303,000 mothers die globally, and one in every 180 is at risk from maternal causes. Developing regions account for 99% of maternal deaths. Maternal near miss (MNM) resulted in long-term consequences. A systematic review and meta-analysis was performed to assess the prevalence and predictors of maternal near miss in Ethiopia from January 2015 to March 2023. Methods A systematic review and meta-analysis cover both published and unpublished studies from different databases (PubMed, CINHAL, Scopus, Science Direct, and the Cochrane Library) to search for published studies whilst searches for unpublished studies were conducted using Google Scholar and Google searches. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used. Duplicated studies were removed using Endnote X8. The paper quality was also assessed based on the JBI checklist. Finally, 21 studies were included in the study. Data synthesis and statistical analysis were conducted using STATA Version 17 software. Forest plots were used to present the pooled prevalence using the random effect model. Heterogeneity and publication bias was evaluated using Cochran's Q test, (Q) and I squared test (I2). Subgroup analysis based on study region and year of publication was performed. Result From a total of 705 obtained studies, twenty-one studies involving 701,997 pregnant or postpartum mothers were included in the final analysis. The national pooled prevalence of MNM in Ethiopia was 140/1000 [95% CI: 80, 190]. Lack of formal education [AOR = 2.10, 95% CI: 1.09, 3.10], Lack of antenatal care [AOR = 2.18, 95% CI: 1.33, 3.03], history of cesarean section [AOR = 4.07, 95% CI: 2.91, 5.24], anemia [AOR = 4.86, 95% CI: 3.24, 6.47], and having chronic medical disorder [AOR = 2.41, 95% CI: 1.53, 3.29] were among the predictors of maternal near misses from the pooled estimate. Conclusion The national prevalence of maternal near miss was still substantial. Antenatal care is found to be protective against maternal near miss. Emphasizing antenatal care to prevent anemia and modifying other chronic medical conditions is recommended as prevention strategies. Avoiding primary cesarean section is recommended unless a clear indication is present. Finally, the country should place more emphasis on strategies for reducing MNM and its consequences, with the hope of improving women's health.